1999
DOI: 10.1007/s004670050609
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal hypercoagulation and hypofibrinolysis is present in childhood peritonitis

Abstract: An increased rate of obstruction of peritoneal dialysis catheters is observed during peritonitis. Hypercoagulation and hypofibrinolysis may explain this increased occurrence. We studied plasminogen activator inhibitor type 1 antigen (PAI-1), tissue-type plasminogen activator antigen (t-PA), D-dimer (DD), plasmin-alpha2-antiplasmin complexes (PAP), and thrombin-antithrombin III complexes (TAT) in 7 children with peritonitis (group A) and 12 children during stable peritoneal dialysis (group B). Albumin, beta2-mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 8 publications
0
19
0
1
Order By: Relevance
“…Adjuvant therapy Patients with extremely cloudy effluent may benefit from the addition of low-dose heparin (500–1000 U/L) into the dialysate as it can help prevent occlusion of the catheter due to fibrin, which is often present as a result of the inflammatory process [96]. As infants receiving CPD with peritonitis can lose substantial amounts of gamma globulin across an inflamed peritoneum, they may benefit from intravenous immunoglobulin (Ig) therapy, especially if they have low measured IgG levels and/or they appear septic [97, 98].…”
Section: Management Of Peritonitismentioning
confidence: 99%
“…Adjuvant therapy Patients with extremely cloudy effluent may benefit from the addition of low-dose heparin (500–1000 U/L) into the dialysate as it can help prevent occlusion of the catheter due to fibrin, which is often present as a result of the inflammatory process [96]. As infants receiving CPD with peritonitis can lose substantial amounts of gamma globulin across an inflamed peritoneum, they may benefit from intravenous immunoglobulin (Ig) therapy, especially if they have low measured IgG levels and/or they appear septic [97, 98].…”
Section: Management Of Peritonitismentioning
confidence: 99%
“…Elevated levels of PAI-1 are present in the peritoneal tissue of surgical patients with intra-abdominal adhesions (11,12). Expression of PAI-1 is also intensified and widely distributed in submesothelial tissue during peritonitis in PD patients (13,14).…”
mentioning
confidence: 99%
“…Both serum and dialysate levels of AT-III were found to be high in patients with CAPD, although there was a continuous loss of large amounts of AT-III within the dialysate fluid, and this was explained as being due to some compensatory mechanisms [7,8]. It was also shown that the levels of thrombin-antithrombin complex increase, whereas tissueplasminogen activator (t-PA) and plasminogen activator inhibitor 1 (PAI-1) decrease in patients with peritonitis who were on CAPD [4].…”
Section: Introductionmentioning
confidence: 89%
“…The efficiency of heparin, which is used to decrease fibrin production in patients with peritonitis, may be limited [3,4]. It was shown in previous studies that thrombin production, which has an important role in fibrin production, increases in patients with severe peritonitis [4]. However, the effect of antithrombin III (AT-III), which inactivates thrombin formation by making a complex with thrombin and antithrombin, is not entirely known in peritonitis.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation